2009
DOI: 10.1016/j.cgh.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

A Very Low-Carbohydrate Diet Improves Symptoms and Quality of Life in Diarrhea-Predominant Irritable Bowel Syndrome

Abstract: Background & Aims-Patients with diarrhea-predominant IBS (IBS-D) anecdotally report symptom improvement after initiating a very low-carbohydrate diet (VLCD). This is the first study to prospectively evaluate a VLCD in IBS-D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 17 publications
1
72
0
1
Order By: Relevance
“…Adult studies have shown clinical improvement of FD and reflux after weight Childhood obesity and functional disorders S Bonilla et al loss, 28,29 but there is conflicting evidence for other FGIDs. 30 In summary, we found that obesity is associated with poor long-term outcome in children with FGIDs. Obesity is associated with persistence of GI symptoms and disability at long-term follow-up in children with abdominal pain-related FGIDs.…”
Section: Discussionmentioning
confidence: 64%
“…Adult studies have shown clinical improvement of FD and reflux after weight Childhood obesity and functional disorders S Bonilla et al loss, 28,29 but there is conflicting evidence for other FGIDs. 30 In summary, we found that obesity is associated with poor long-term outcome in children with FGIDs. Obesity is associated with persistence of GI symptoms and disability at long-term follow-up in children with abdominal pain-related FGIDs.…”
Section: Discussionmentioning
confidence: 64%
“…Most patients with IBS believe diet plays a significant role in their symptoms and 63% desire to know what foods to avoid (28)(29)(30)(31). More than 60% of IBS patients report worsening of symptoms following food ingestion; 28% within 15 min after eating and 93% within 3 h (32).…”
Section: Diet In Ibs Patientsmentioning
confidence: 99%
“…On average, IBS patients miss 13.4 days of work and school per year (17,23). IBS patients have a high percentage of losing a job, quitting work or turning down a promotion, and work fewer hours as a result of their condition (26,27). More than 60% of IBS patients report worsening of symptoms following food ingestion; 28% within 15 min of eating and 93% within 3 h (28).…”
Section: Introductionmentioning
confidence: 99%